cis-Cyclohexane-1,4-dicarboxylic acid - Wang, Yan-Qin (International Union of Crystallography, 2009)
In the title compound, C(8)H(12)O(4), the two carboxyl groups are on the same side of the cyclohexane ring and the ring adopts a chair conformation. Adjacent molecules related by an inversion centre are linked by pairs of O—H⋯O hydrogen bonds, forming a zigzag chain along [1[Image: see text] [Image: see text]].